2006
DOI: 10.1111/j.1442-2042.2006.01430.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutcracker phenomenon: A new diagnostic method of multislice computed tomography angiography

Abstract: Objective:We evaluated 3-D computed tomography angiography (3-D CTA) in the diagnosis of the nutcracker phenomenon, and its significance in postoperative follow up. Patients and Methods: Three-dimensional CTA was used to compare the anatomical relations of the left renal vein with the aorta and the superior mesenteric artery in patients with the nutcracker phenomenon and in a control group. Four patients with the nutcracker phenomenon received a surgical procedure of the transposition of the left renal vein. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 10 publications
1
37
0
6
Order By: Relevance
“…97,98 Later studies reported that it was close to 90° in healthy individuals, with angles smaller than half that in patients with NCP. 21,23,24 Other studies suggested half smaller numbers for normal and NCP variants, consistent with earlier reports. 65,99 Despite this reported variability, smaller AMAs have been associated with NCP compared with healthy controls; however, when the third portion of the duodenum courses between the aorta and the SMA (duodenal interposition), the LRV compression occurs even with a larger AMA.…”
Section: Normal Anatomic and Physiologic Findingssupporting
confidence: 80%
See 2 more Smart Citations
“…97,98 Later studies reported that it was close to 90° in healthy individuals, with angles smaller than half that in patients with NCP. 21,23,24 Other studies suggested half smaller numbers for normal and NCP variants, consistent with earlier reports. 65,99 Despite this reported variability, smaller AMAs have been associated with NCP compared with healthy controls; however, when the third portion of the duodenum courses between the aorta and the SMA (duodenal interposition), the LRV compression occurs even with a larger AMA.…”
Section: Normal Anatomic and Physiologic Findingssupporting
confidence: 80%
“…18,23,100,105,106 Renal angiography shows delayed venous washout from the left kidney. Intravenous urograms and retrograde pyelograms often reveal normal findings, even in the presence of unilateral hematuria on cystoscopy 21,24,107 ; however, notching from varicosities of the renal pelvis and ureters may be seen. 47,56,108 Attempts to validate LRV diameter ratios have been unsuccessful given that LRV dilatation may be a normal variant.…”
Section: Normal Anatomic and Physiologic Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter has been described as in the "nutcracker syndrome," where compression of the left renal vein between the superior mesenteric artery and the anterior aorta can lead to venous hypertension and gonadal varices. 7 Most renal vein aneurysms involve the left renal vein, which undergoes more complicated embryological development because of its increased length. 5 The donor in this case underwent a left nephrectomy, although no signs of the nutcracker syndrome were present on preoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The most accepted hypotheses proposed to explain the compression are posterior renal ptosis, abnormal high course of the LRV or an abnormal origin of the SMA from the aorta (30,33).…”
Section: Nutcracker Syndrome (Ns)mentioning
confidence: 99%